2019
DOI: 10.3389/fenvs.2019.00120
|View full text |Cite
|
Sign up to set email alerts
|

Effect-Directed Analysis of Ah Receptor-Mediated Potencies in Microplastics Deployed in a Remote Tropical Marine Environment

Abstract: To facilitate the study of potential harmful compounds sorbed to microplastics, an effect-directed analysis using the DR CALUX ® assay as screening tool for Aryl hydrocarbon receptor (AhR)-active compounds in extracts of marine deployed microplastics and chemical analysis of hydrophobic organic compounds (HOCs) was conducted. Pellets of three plastic polymers [low-density polyethylene (LDPE), high-density polyethylene (HDPE) and high-impact polystyrene (HIPS)] were deployed at Heron Island in the Great Barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Our findings highlight that degrading and largely additive-free pre-production polymers have the potential to induce adverse effects on whole organisms, particularly PE; however, stronger adverse effects were observed if the polymers contained additives or other chemicals. As a future step, advanced chemical analytical tools, e.g., effect-directed analysis combined with non-target screening, would be necessary to resolve the chemicals causing these effects [44,45]. Therefore, the application of effect-based tools provides a reliable strategy to assess potential environmental risks from potentially hazardous materials like plastics.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight that degrading and largely additive-free pre-production polymers have the potential to induce adverse effects on whole organisms, particularly PE; however, stronger adverse effects were observed if the polymers contained additives or other chemicals. As a future step, advanced chemical analytical tools, e.g., effect-directed analysis combined with non-target screening, would be necessary to resolve the chemicals causing these effects [44,45]. Therefore, the application of effect-based tools provides a reliable strategy to assess potential environmental risks from potentially hazardous materials like plastics.…”
Section: Discussionmentioning
confidence: 99%
“…In step-wise approaches, the complexity of the sample is reduced and candidates for an observed toxic effect are attempted to be identified. These approaches have been applied to plastics to a limited extent (Schönlau et al 2019) and offer possibilities of addressing toxicity and chemical identification in a complex setting. Additionally, new effects monitoring tools can be used to determine contaminant burdens across species.…”
Section: Longmentioning
confidence: 99%
“…Microplastics are a contaminant of emerging concern in freshwater ecosystems (Lambert and Wagner 2018;Rochman and Hoellein 2020). They can cause a range of adverse effects in freshwater biota at multiple levels of biological organization, due in part to their inherent complexity (e.g., size, polymer, morphology) (Rochman et al 2019;Bucci et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics are a contaminant of emerging concern in freshwater ecosystems (Lambert and Wagner 2018;Rochman and Hoellein 2020). They can cause a range of adverse effects in freshwater biota at multiple levels of biological organization, due in part to their inherent complexity (e.g., size, polymer, morphology) (Rochman et al 2019;Bucci et al 2020). Studies that investigate microplastics as a single stressor (e.g., Li et al 2024;Malinowski et al 2023;Schür et al 2023) have demonstrated that microplastics are impacting freshwater ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation